The Strategies Analysis of Corporate University in the Government Agencies in Indonesia - Perdhana Ari Sudewo (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2022)
Changes in the world's landscape with massive digital developments affect learning and development strategies of human resources in every organization, including the Government Agencies. In Indonesia, changes in ASN competency management as mandated by the Law on ASN also encourage changes in the learning and development process in education and training units, marked by the emergence of Corporate Universities in Government Agencies. Using the concept and generic strategy approach of Corporate University developed by Radermarkers (2014), this research intends to analyze the learning strategies developed by Corporate University in Government Agencies in Indonesia. The research method is carried out with a literature study approach with data and information from the Corporate University strategic plan as the main data source. From the analysis of concepts and strategies for six Corporate Universities, it can be concluded that the school strategy is the strategy chosen by the majority of Corporate Universities in Government Agencies, compared to the college strategy and the academy strategy. Various concepts and strategies of Corporate University in this research are expected to reference other Government Agencies that will develop Corporate University as a strategy in developing ASN competencies in Indonesia.